DNA flow cytometric analysis in variable types of hydropic placentas - Fatemeh Atabaki pasdar; Alireza Khooei; Alireza Fazel; Maryam Rastin; Nafise Tabasi; Tahmineh Peirouvi; Mahmoud Mahmoudi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Differential diagnosis between complete hydatidiform mole, partial hydatidiform mole and hydropic abortion, known as hydropic placentas is still a challenge for pathologists but it is very important for patient management. Objective: We analyzed the nuclear DNA content of various types of hydropic placentas by flowcytometry. Materials and Methods: DNA ploidy analysis was performed in 20 non-molar (hydropic and non-hydropic spontaneous abortions) and 20 molar (complete and partial moles), formalin-fixed, paraffin-embedded tissue samples by flow cytometry. The criteria for selection were based on the histopathologic diagnosis. Results: Of 10 cases histologically diagnosed as complete hydatiform mole, 9 cases yielded diploid histograms, and 1 case was tetraploid. Of 10 partial hydatidiform moles, 8 were triploid and 2 were diploid. All of 20 cases diagnosed as spontaneous abortions (hydropic and non-hydropic) yielded diploid histograms. Conclusion: These findings signify the importance of the combined use of conventional histology and ploidy analysis in the differential diagnosis of complete hydatidiform mole, partial hydatidiform mole and hydropic abortion.